2020
DOI: 10.1123/jsm.2019-0381
|View full text |Cite
|
Sign up to set email alerts
|

Row! Row! Row Your Boat! Transformative Value Cocreation and Codestruction in Elite and Olympic Rowers

Abstract: This article explores in-depth interviews with elite and Olympic rowers to examine transformative value, dimensions of value creation that generate uplifting change and greater well-being, and the resources integrated to cocreate or destroy these benefits. This study is the first to demonstrate transformative value in a sport setting, extending theorizing on value in sport studies and demonstrating the utility of the multidimensional frameworks with five dimensions: emotional, social, functional, epistemic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
2
9
0
1
Order By: Relevance
“…The results show (Table VI, Figure 2) that three capitalization support dimensions (i.e., academic support H1a, self-development support H1c, and place support H1d) directly influence student-athletes' well-being and indirectly enhance their performance. The establishment of a direct link between support and well-being confirms and extends the TSSR findings of Mulcahy and Luck (2020) and the TSR findings of Parkinson et al (2017). Both these studies found that social support could impact well-being.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results show (Table VI, Figure 2) that three capitalization support dimensions (i.e., academic support H1a, self-development support H1c, and place support H1d) directly influence student-athletes' well-being and indirectly enhance their performance. The establishment of a direct link between support and well-being confirms and extends the TSSR findings of Mulcahy and Luck (2020) and the TSR findings of Parkinson et al (2017). Both these studies found that social support could impact well-being.…”
Section: Discussionsupporting
confidence: 83%
“…Place support was a service dimension with a significant positive impact on studentathlete well-being. In line with Mulcahy and Luck's (2020) suggestions, it is important for student-athlete services to create a third place using elements such as specialized university gyms or student-athlete lounges (e.g., areas to study/relax) designed to help establish a sense of belonging, attachment, and identity. Indeed, studies in other higher education service contexts stress the importance of place attachment and identity for cohorts like first-year students (Chow and Healy, 2008).…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the theoretical and empirical insights produced by the eight articles included in this special issue provide implications that can transform how sport services are produced and delivered to optimize the personal and collective well-being of elite athletes (MacIntosh et al, 2020;Mulcahy & Luck, 2020;, student athletes (Kim et al, 2020), volunteers (Wicker & Downward, 2020), spectators (Katz et al, 2020), and parents of youth sport participants (Misener, 2020;Trussell, 2020). The authors of these articles also examine a variety of sport service contexts, ranging from community youth sport programs to an international sport event, and adopt both hedonic and eudaimonic approaches to understanding the well-being outcomes of sport services.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study extends the literature on value cocreation at sports events by exploring the mechanisms underlying the influence of value cocreation activities involving sports spectators. A previous study examined transformative value cocreation for Olympic athletes to improve player well-being [76]. Horbel [5] introduced the theory of value cocreation in sports events and explored value cocreation activities involving television audiences of sports events and the mechanisms underlying the effects of such activities.…”
Section: Eoretical Implicationsmentioning
confidence: 99%